TEACHING SPEECH FORMATION TO PRESCHOOL-AGE DYSARTIC CHILDREN (American Journal of Pedagogical and Educational Research, 2023)
The speech function is one of the most important mental functions of a person. In the process of speech development, the highest forms of cognitive activity, the ability to think conceptually, are formed. Mastering the ability to communicate verbally creates the necessary conditions for a person's concrete social relations, as a result of which the child's ideas about the surrounding reality are formed and improved, and the forms of its reflection are improved.